Culture matters: turn to the study of cultural factors of economic development in socio-humanitarian knowledge - Haurylik, Aksana N. (Journal of the Belarusian State University. Sociology, 2023)
The article provides an analytical review of modern approaches to the study of the influence of cultural factors on the economic development of society. The reasons for the actualisation of research in this direction are revealed, including activation of globalisation processes, promotion of goods and services of companies in international markets, problems of building a market economy in non-Western countries, changing ideas about the vectors of modernisation, as well as the turn to the study of cultural factors of social development in socio-humanitarian sciences. It becomes obvious that the economy is not an autonomous area, but a part of the whole – a subsystem of society, connected with other subsystems, including social and cultural ones. The key questions on which the scientific discussion is unfolding are highlighted: what non-economic factors have the greatest impact on economic processes; how cultural factors are amenable to quantitative measurement procedures, what methods should be used; whether culture is a resource for innovation, a catalyst for reforms or an obstacle to modern transformations; whether it is possible to have a transformative impact on culture in order to improve the economic efficiency of economic entities. The article substantiates the priority of the sociological approach to the study of the mechanisms of interaction between culture and economy.
Keywords: culture; cultural factors; non-economic factors; sphere of society; economy; economic culture